The gut microbiota-independent virulence of noninvasive bacterial pathogen Citrobacter rodentium. - Yue Liu; Dongqing Xu; Songwei Guo; Shuyu Wang; Hua Ding; Catherine Siu; Fengyi Wan (PLoS Pathogens)
Attaching and effacing (A/E) bacterial pathogens consist of human pathogens enteropathogenic Escherichia coli, enterohemorrhagic E. coli and their murine equivalent Citrobacter rodentium (CR). Emerging evidence suggests that the complex pathogen-microbiota-host interactions are critical in conferring A/E pathogen infection-induced severe symptoms and lethality in immunocompromised hosts; however, the precise underlying mechanisms remain enigmatic. Here we report that CR infection causes severe colitis and mortality in interleukin 22 knockout (Il22-/-) and Rag1 knockout (Rag1-/-) mice under germ-free (GF) conditions. In a gut microbiota-independent manner, CR colonizes in GF Il22-/- and Rag1-/- animals, triggers colonic epithelial tissue damage and systemic dissemination of CR, and results in lethal infections. Pretreatment with cefoxitin, a broad-spectrum antibiotic, exacerbates CR-induced colitis and lethality in specific-pathogen-free (SPF) Il22-/- and Rag1-/- mice. Together our results reveal that CR possesses a gut microbiota-independent virulence, which is better illustrated during infections in immunocompromised hosts associated with severe outcomes.